Answer :

Answer:

Step-by-step explanation:

m (x) = (x+ 5) / (x -1)        and     n(x) = x - 3.

[tex]m(x) = \dfrac{x+5}{x-1}[/tex]

Hence

[tex]m(n) = \dfrac{n+5}{n-1}[/tex]

but n is a function and n = x-3. Now, replace value of n on m (n)

[tex](m(n))= \dfrac{(x-3)+5}{(x-3)-1}[/tex]

simplify it

[tex](m\bullet n)(x) =\dfrac{x+2}{x-4}\\[/tex]

since (m . n) (x)  is a fraction function, its domain will be all x such that the denominator is NOT 0. That is

[tex]x-4\ne 0\rightarrow x\ne 4[/tex]

among options, only C has the same denominator with [tex](m\bullet n)(x)[/tex]

Hence their domains are the same.